Efficacy of atorvastatin therapy in prevention of postoperative atrial fibrillation in patients with ischemic heart disease - O. A. Rubanenko (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2015)
Aim. To evaluate the efficacy of atorvastatin therapy in prevention of atrial fibrillation (AF) development after coronary artery bypass graft (CABG) surgery in patients with ischemic heart disease (IHD) with the assessment of inflammation, sheer stress and myocardial injury indicators. Material and methods. The study included 105 patients with IHD who were divided into two groups: patients of group 1 were treated with atorvastatin (59 patients, 81% males, mean age 62.1±7.5 years); patients of group 2 received no HMG-CoA reductase inhibitors (46 patients, 89% males, and mean age 61.7±8.1 years). Results. Postoperative AF occurred more often in patients of group 2 (41.3% vs 16.9%; р=0.047). Laboratory analysis revealed the following: the levels of total leukocytes, interleukin-8, interleukin-10, C-reactive protein, fibrinogen, superoxide dismutase and troponin did not different significantly among the patients of two groups. Interleukin-6 level in preand postoperative period was significantly higher in patients of group 2 (35.4±28.5 pg/ml vs 24.1±14.8 pg/ml, р=0.03; 63.7±54.8 pg/ml vs 50.7±40.8 pg/ml, р=0.04, respectively). Conclusion. Our study has shown that atorvastatin therapy contributed to the reduction of number of new cases of AF after CABG in patients with IHD. At that, the efficacy of atorvastatin therapy correlated with the size of left atrium and the severity of inflammatory response. Patients with atorvastatin therapy had significantly lower interleukin-6 level, as a proinflammatory marker, in preand postoperational period as compared with the patients without such treatment.